Hematological studies on the effect of environmental stress (Especially diesel generator caused air pollution) on cockerel bird. - Dayal, Agam; Dubey, Rajesh Kumar (International Multidisciplinary Research Journal, 2012)
Hematological changes in Cockerel birds exposed to diesel generator exhaust for 30 and 60minutes; at different distance levels i.e. for 2ft, 6ft and 10ft, for different length of period’s i.e, 7days, 14days, 21days and 28days and the values were compared with control groups. Each group comprising six birds and values were presented as mean ± S.E and the values were analyzed by F’ test at 5% degree level of freedom.Blood samples collected from brachial vein were processed for different hematological parameters viz: - Total erythrocyte count (TEC), Hb%, Packed cell volume (PCV), Total leukocyte count (TLC) were investigated. Total erythrocyte counts were found to be significantly lower in exposed groups. Hb% also significantly decreased. Packed cell volume and Total leukocyte count was significantly increased.